2008
DOI: 10.1158/1078-0432.ccr-07-5123
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer with Epidermal Growth Factor Receptor Exon 20 Mutations Is Associated with Poor Gefitinib Treatment Response

Abstract: Purpose: Clinical reports about responsiveness to gefitinib treatment in patients of non-small cell lung cancer (NSCLC) with mutations in exon 20 of epidermal growth factor receptor (EGFR) are limited. To increase understanding of the influence of exon 20 mutations on NSCLC treatment with gefitinib, we investigated the clinical features of lung cancer in patients with exon 20 mutations and analyzed the gefitinib treatment response. Experimental Design: We surveyed the clinical data and mutational studies of NS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
213
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 279 publications
(230 citation statements)
references
References 46 publications
(40 reference statements)
14
213
1
2
Order By: Relevance
“…15,67 The most important mutation in exon 20 is T790M, which is associated with a small fraction of adenocarcinomas with primary resistance to EGFR TKI and over one-half of the patients with acquired resistance to EGFR TKI ( Figure 2). 12,[67][68][69][70][71] A comprehensive literature review by Yamamoto et al 33 indicated that 569 mutations were found in 2880 lung cancer patients (20%). The distribution of EGFR mutations was as follows: 48% in exon 19, 43% in exon 21, 4% in exon 20, and 3% in exon 18.…”
Section: Egfr Mutationsmentioning
confidence: 99%
See 4 more Smart Citations
“…15,67 The most important mutation in exon 20 is T790M, which is associated with a small fraction of adenocarcinomas with primary resistance to EGFR TKI and over one-half of the patients with acquired resistance to EGFR TKI ( Figure 2). 12,[67][68][69][70][71] A comprehensive literature review by Yamamoto et al 33 indicated that 569 mutations were found in 2880 lung cancer patients (20%). The distribution of EGFR mutations was as follows: 48% in exon 19, 43% in exon 21, 4% in exon 20, and 3% in exon 18.…”
Section: Egfr Mutationsmentioning
confidence: 99%
“…Exons 18-21 in the tyrosine kinase region of the EGFR gene are scaled up; a detailed list of EGFR mutations in these exons associated with sensitivity (green) or resistance (orange) to EGFR TKI. 6,12,[67][68][69][70][71][80][81][82][83][84]195 The frequency of the mutations is labeled to the side of the color-coded bars. The most prevalent EGFR mutations are in-frame deletions of exon 19 (45%), followed by L858R substitution in exon 21 (41%).…”
Section: Egfr Mutationsmentioning
confidence: 99%
See 3 more Smart Citations